High Carbon Mineralization Rates in Subseafloor Hadal Sediments—Result of Frequent Mass Wasting. (19th September 2022) - Zabel, M.; Glud, R. N.; Sanei, H.; Elvert, M.; Pape, T.; Chuang, P.‐C.; Okuma, E.; Geprägs, P.; Kölling, M.
Abstract: In the past 20 years, the exploration of deep ocean trenches has led to spectacular new insights. Even in the deepest canyons, an unusual variety of life and unexpectedly high benthic oxygen consumption rates have been detected while microbial processes below the surface of the hadal seafloor remains largely unknown. The information that exist comes from geophysical measurements, especially related to seismic research, and specific component analyses to estimate the carbon export. In contrast, no information is available on metabolic activities in deeper buried sediments of hadal environment. Here we present the first pore water profiles from 15 up to 11 m long sediment cores recovered during three expeditions to two hadal zones, the Japan Trench and the Atacama Trench. Despite low levels of organic debris, our data reveal that rates of microbial carbon turnover along the trench axes can be similar to those encountered in much shallower and more productive oceanic regions. The extreme sedimentation dynamics, characterized by frequent mass wasting of slope sediments into the trenches, result in effective burial of reactive, microbially available, organic material. Our results document the fueling of the deep hadal biosphere with bioavailable material and thus provide important understanding on the function of deep‐sea trenches and the hadal carbon cycle. Plain Language Summary: For a long time, it was assumed that in water depths below 6, 000 m, biological species diversity and microbial activity is very low. Recent studies could already provide clear evidence that significant degradation of organic material occurs even at the seafloor surface in deep‐sea trenches. No comparable information is available yet about the situation below the surface layer. Here, data are presented for the first time that help to close this knowledge gap. Based on geochemical parameters, it can be proven that very active degradation processes also take place in the deeper buried layers in deep‐sea trenches. Rates correspond in magnitude to sediments from shallower water depths with considerably higher contents of organic material. The authors attribute this finding primarily to sedimentation dynamics in deep‐sea trenches. The steep flanks of trenches, sometimes associated with seismic activity, repeatedly favor the sliding of large sediment packages into basins along trench axes. Rapid burial removes less degraded, and thus more microbially available material from oxic surface and preserves it for subsequent processes such as sulfate reduction. The unique results provide important new insights into the function of deep‐sea trenches and the hadal carbon cycle. Key Points: Hadal subseafloor pore water profiles from the Japan Trench and Atacama Trench document unexpectedly high microbial turnover rates Frequent alternations between hemipelagic sedimentation and mass wasting lead to high burial efficiency of reactive organic carbon Microbial activities in deep‐sea trenches may be similar to those at the edge of high‐production areas